THE EFFECT OF OWNERSHIP STRUCTURES AND CEO POWER TO CSR PERFORMANCE MODERATED BY PROFITABILITY - Rachmawati, Ayu; Roekhudin, Roekhudin; Prastiwi, Arum (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Effect of Ownership Structures and CEO Power to CSR Performance Moderated by Profitability. This study aimed to analyze effects which affect CSR Performance in Indonesia’s companies. Ownership structures which are used in this study are family ownership and managerial ownership in a company. Samples are companies listed in Indonesia Stock Exchange (IDX) in 2017-2019, selected using probability sampling technique and purposive sampling method. Secondary data used and collected from Sustainability Report in every selected company. Data were analyzed by SPSS 26.0. This study found that family ownership in public companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019, except companies engaged in finance support the realization of CSR Performance. This study does not support that managerial ownership and CEO power affect CSR Performance. Profitability strengthens the positive relationship of managerial ownership to CSR Performance, but does not support that profitability strengthens the positive relationship of family ownership and CEO power to CSR Performance. Keywords: CSR Performance, Ownership Structure, CEO Power, Profitability